2021
DOI: 10.1155/2021/6690564
|View full text |Cite
|
Sign up to set email alerts
|

Darmok and Jalad at the Psych Ward: A Case Demonstration of How to Creatively Communicate with a 19-Year-Old Patient with Autism Spectrum Disorder

Abstract: Difficulties in communication often arise between individuals with autism spectrum disorder and their treating physicians because both sides struggle to find a common ground. The story of Darmok and Jalad at Tanagra from Star Trek: The Next Generation nicely exemplifies how two populations that spoke different languages were still able to find a creative way to communicate with each other. This story is used as a metaphor to illustrate how a novel connection was made with a 19-year-old patient with autism spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Additionally, a care planway can support speedy diagnosis, decrease anxiety and better equip staff to provide a person‐centred approach to their care (Gray & Roback, 2020; Gupta et al, 2019; Kopecky et al, 2013; Kouo et al, 2021). Studies have shown that the care experience has been improved when using a care pathway (Ailey et al, 2019; Broder‐Fingert et al, 2016; Kim et al, 2021; Kirsch et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a care planway can support speedy diagnosis, decrease anxiety and better equip staff to provide a person‐centred approach to their care (Gray & Roback, 2020; Gupta et al, 2019; Kopecky et al, 2013; Kouo et al, 2021). Studies have shown that the care experience has been improved when using a care pathway (Ailey et al, 2019; Broder‐Fingert et al, 2016; Kim et al, 2021; Kirsch et al, 2018).…”
Section: Resultsmentioning
confidence: 99%